Shadow target - Ricciardi, David (New York Berkley, 2022)
Jake doesn't know who is trying to kill him, and he doesn't know why, but it's a threat he can't ignore. When his small plane crashes in the Alps, Jake is the only survivor. A rescue helicopter soon arrives, but the men inside are not there to save anyone. They are determined to complete the murderous job they started. Jake escapes from the mountainside death trap, but it won't be the only attempt on his life. If he's to have any chance of surviving, he'll have to find out who's behind the killings. But the circle of people Jake can trust is small, as he suspects someone from the Agency is feeding his every move to the people who are trying to end his life. Jake's quest takes him to the cathedrals of Paris and the rain-slicked streets of London. He makes contact with old friends and new enemies along the way, but his true nemesis may be closer than he imagines.
112664
Keywords: Keller, Jake -- (Fictitious character) -- Fiction; United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; United States. -- Central Intelligence Agency; Assassination -- Fiction; Intelligence officers -- Fiction; Employees; Crime Action and Adventure; Europe -- Fiction; Paris (France) -- Fiction; London (England) -- Fiction; England -- London; France -- Paris; Fiction; Spy fiction; Thrillers (Fiction); Suspense fiction